1992
DOI: 10.1128/jb.174.24.7910-7918.1992
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of a cyanobacterial ilvC gene encoding acetohydroxyacid isomeroreductase

Abstract: Acetohydroxyacid isomeroreductase (AHAIR) is the shared second enzyme in the biosynthetic pathways leading to isoleucine and valine. AHAIR is encoded by the ilvC gene in bacteria. A 1,544-bp fragment of genomic DNA containing the ilvC gene was cloned from the cyanobacterium Synechocystis sp. strain PCC 6803, and the complete nucleotide sequence was determined. The identity of the gene was established by comparison of the nucleotide and derived peptide sequences with those of other ilvC genes. The highest degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…meliloti --------------------------------------------------E --------------------------FLAQ --------------------------FLAQ --------- R. meliloti E.coli between the acetohydroxy acid isomeroreductases from S. oleracea (Dumas et al, 1991), A. thaliana (Curien et al, 1993), Saccharomyces cerevisiae (Petersen & Holmberg, 1986), Neurospora crassa (Sista & Bowman, 1992), Lactobacillus lactis (Godon et al, 1992), Synechocystis sp. (Rieble & Beale, 1992), Rhizobium meliloti (Aguilar & Grasso, 1991), and E. coli (Wek & Hatfield, 1986). They define the conserved domains I-V. A conserved sequence not found in the R. meliloti sequence was underlined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…meliloti --------------------------------------------------E --------------------------FLAQ --------------------------FLAQ --------- R. meliloti E.coli between the acetohydroxy acid isomeroreductases from S. oleracea (Dumas et al, 1991), A. thaliana (Curien et al, 1993), Saccharomyces cerevisiae (Petersen & Holmberg, 1986), Neurospora crassa (Sista & Bowman, 1992), Lactobacillus lactis (Godon et al, 1992), Synechocystis sp. (Rieble & Beale, 1992), Rhizobium meliloti (Aguilar & Grasso, 1991), and E. coli (Wek & Hatfield, 1986). They define the conserved domains I-V. A conserved sequence not found in the R. meliloti sequence was underlined.…”
Section: Methodsmentioning
confidence: 99%
“…To identify essential domains or residues of the enzyme that participate in metal ion cofactor binding, the predicted amino acid sequences of plant acetohydroxy acid isomer-oreductase have been aligned to the known sequences of corresponding enzymes from fungi (Petersen & Holmberg, 1986;Sista & Bowman, 1992) and bacteria (Blazey & Bums, 1984; Wek & Hatfield, 1986;Aguilar & Grasso, 1991;Godon et al, 1992;Rieble & Beale, 1992) (Figure 2). This sequence comparison indicated five regions of identity that have been designated in this paper as domains I-V. Domain I is similar to the fingerprint region of the NADPH-binding site found in a large number of NADPH-dependent oxidoreductases (Dumas et al, 1991).…”
mentioning
confidence: 99%
“…In Synechocystis PCC6803, genes have been identified for an acetohydroxy acid isomeroreductase (Fig. 1) (Rieble and Beale, 1992) and for two potential large subunits (ORFs sll1981 and slr2088 ) and a small subunit (ORF sll0065 ) of ALS/AHAS (Kaneko et al ., 1996). The slr2088 ‐encoded protein shows high homology to the AHAS enzyme of S. platensis (Milano et al ., 1992).…”
Section: Introductionmentioning
confidence: 99%
“…As the FBG concentration increased in T2DM patients, the level of pyruvic acid was increased, which would lead to an increase in 2‐acetolactate 39 . Then, under the action of various active enzymes, such as acetohydroxy acid isomeroreductase and branched‐chain amino acid transaminase, 2‐acetolactate undergoes a biosynthetic pathway to form valine and isoleucine 40 . The results of this study showed that the FC values of L‐valine and L‐isoleucine were 1.21 and 1.22, which conformed to the above pathway.…”
Section: Discussionmentioning
confidence: 99%